The problem-based learning e-module of planes using Kvisoft Flipbook Maker for elementary school students - Dyah Triwahyuningtyas; Ayu Setyo Ningtyas; Sri Rahayu (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2020)
The conduct of the present study is encouraged by the needs to afford the teaching materials in the form of an electronic learning module or e-module that can be combined with the problem-based learning approach in order to expand the students’ insights in and draw the students’ interest toward Mathematics. These needs should be afforded because the present teaching materials used in the learning process are still conventional and, consequently, the students become easily bored. Departing from this elaboration, the objective of the present study is to develop the teaching materials, especially in the subject “Simple Planes” in the Third Grade, and to measure the validity, the practicality, and the effectiveness of the media that have been developed. In conducting the study, the ADDIE model, standing for Analysis, Design, Development, Implementation, and Evaluation, had been adopted and the data were gathered by means of validation sheet and response questionnaire. After the data had been gathered, the data were analysed by using the qualitative and the quantitative data analysis technique. The results of the study show that the problem-based learning (PBL)-based planes e-module using the KVISFOT Flipbook Maker that has been developed is already valid with the mean score of 85.82%. At the same time, the results of the response category show that the problem-based learning (PBL)-based planes e-module using the KVISFOT Flipbook Maker that has been developed is already good with the mean score 3.78. Furthermore, the mean score from the effectiveness test using the evaluation test for the Third-Grade students is 90.47. Therefore, it can be concluded that the e-module is able to improve the students’ learning motivation so that the learning process can proceed fluently.